2018
DOI: 10.1186/s12916-018-1126-3
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the cost-effectiveness of pay-for-performance in primary care in the UK

Abstract: BackgroundIntroduced in 2004, the United Kingdom’s (UK) Quality and Outcomes Framework (QOF) is the world’s largest primary-care pay-for-performance programme. Given some evidence of the benefits and the substantial costs associated with the QOF, it remains unclear whether the programme is cost-effective. Therefore, we assessed the cost-effectiveness of continuing versus stopping the QOF.MethodsWe developed a lifetime simulation model to estimate quality-adjusted life years (QALYs) and costs for a UK populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…The assessment of the cost-effectiveness of P4P, as well as other health policies and health system interventions, is still in its infancy in both settings, with potentially controversial assumptions and methods needing refinement, but remains crucial. 8,36,[40][41][42] The assessment of whether programme benefits are concentrated in certain population groups has been explored more extensively by researchers in HIC [43][44][45] and there are growing numbers of studies examining this issue in LMIC, 28,46 but more evidence could be helpful to address potential equity concerns. 47…”
Section: Contextmentioning
confidence: 99%
“…The assessment of the cost-effectiveness of P4P, as well as other health policies and health system interventions, is still in its infancy in both settings, with potentially controversial assumptions and methods needing refinement, but remains crucial. 8,36,[40][41][42] The assessment of whether programme benefits are concentrated in certain population groups has been explored more extensively by researchers in HIC [43][44][45] and there are growing numbers of studies examining this issue in LMIC, 28,46 but more evidence could be helpful to address potential equity concerns. 47…”
Section: Contextmentioning
confidence: 99%
“…9,27 After 1 year, for example, Kirschner et al found significant improvement for the process indicators for all chronic conditions affected by their PFP. 28 While one study concluded that it would be more cost effective to discontinue PFP in primary care and 'return all incentive payments to the NHS', 29 removal of financial incentives for certain elements of performance indicators covered by the QOF was associated with an immediate decline in performance on quality measures. 30 In the most recent report on the QOF system, NHS England concluded that it had a modest effect on health outcomes and should be continued, but in a way that enables more holistic, person-centred care.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…The biggest problem has been demonstrating the effectiveness of QOF. Modelling revealed that stopping QOF and leaving the funding within the NHS was more cost effective and that, to improve population health efficiency, QOF needed to be redesigned or replaced with alternative interventions . One study did not show that QOF addressed ethnic disparities in diabetes outcomes despite having the potential to improve inequalities in primary care .…”
Section: Primary Care Experience With Qof: the Pros And Consmentioning
confidence: 99%